Analisis Postur Kerja Pada Proses Pemindahan Pasir Untuk Mengidentifikasi Resiko Kecelakaan Kerja - Ihasanto; Septiana Sulistyorini (SAINTEK : Jurnal Ilmiah Sains dan Teknologi Industri, 2017)
This study aims to know about the assessment of REBA posture method on sand removal work in the prevention of Musculoskletal Disorder. Workers who perform sand removal on UD XYZ are influenced by work posture, work position, and body performance. From the measurement results obtained the value of Rapid Entire Body Assessment REBA is 10, it can be seen the value of 9 is on the score of 8-10 which means that the work of the operator when moving the sand with a shovel has a high risk level and need action as soon as possible. the results obtained in carrying out the sand shoveling activity by repeatedly scoring the REBA score is 9 and it is stated that the activity has the potential to pose a risk of injury to the worker.